Polish workers in the capital area of Iceland - Anna Wojtyńska (2012)
The recent migration to Iceland, especially from Eastern Europe has been first and foremost economically driven. The last economic boom created a big demand for labour that could not be met by the local workforce. The demand was, however, limited to certain sectors as well as being highly gendered. For example, the migration of Polish men was driven primarily by the construction sector while Polish women were finding employment mostly in cleaning, hospitality or care. Importantly, men and women had different experience of social mobility due to migration. As a rule, men continued similar occupations like those performed in Poland, while women more often experienced downward social mobility, engaging in jobs below their qualifications. In my presentation, I will look at the occupational attainment and social mobility of Polish workers in Iceland. What kind of jobs were they predominantly performing in Iceland? How do men and women evaluate their social position when compared to Poland?